Proceedings of the International Conference on Progressive Education (ICOPE 2019) 2020
DOI: 10.2991/assehr.k.200323.114
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Qur’ani Students Worksheet (LKPD) on the Atom Structure Materials in MAN 1 Cirebon City and MAN 1 Plered Cirebon Regency for the Student’s Science-Religious Character Building

Abstract: Chemical Write Students Worksheet (LKPD Chemical) has been applied in MAN 1 Cirebon City and MAN 1 Plered Cirebon Regency. It still not contribute to the student's science-religious character. The LKPD Chemical On the Material Structure of the Atom developed based on the values of the Quran are expected to contribute to the science-religious character of the MAN students. These study aims are to determine: (a) The percentage of the feasibility of the Qurani Students Worksheet, (b) The effectiveness of using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Some studies have suggested that the word dzarrah, which appears multiple times in the Qur'an, can be interpreted as the seed of mustard to analogously explain the size of the atom so that the human mind can imagine it (Azizah & Kisworo, 2020;Badlisyah & Munawwarah, 2017;Sabarni, 2019). Yet, the size of a mustard seed cannot correctly depict atomic size because the atom is much smaller than the mustard seed.…”
Section: Relevance Of Atomic Structure Theory To the Qur'an And Spiri...mentioning
confidence: 99%
“…Some studies have suggested that the word dzarrah, which appears multiple times in the Qur'an, can be interpreted as the seed of mustard to analogously explain the size of the atom so that the human mind can imagine it (Azizah & Kisworo, 2020;Badlisyah & Munawwarah, 2017;Sabarni, 2019). Yet, the size of a mustard seed cannot correctly depict atomic size because the atom is much smaller than the mustard seed.…”
Section: Relevance Of Atomic Structure Theory To the Qur'an And Spiri...mentioning
confidence: 99%